Analisis Bentuk dan Jumlah Bilah pada Fan Chip Pendingin Portable untuk Proses Drilling Logam dengan Flow Simulation - Sifa, Agus; Syahfitri, Shofi; Suwandi, Dedi (Politeknik Negeri Indramayu, 2023)
In the metal drilling process, tool temperature is an important parameter for optimizing cutting conditions, by limiting tool wear so that surface roughness can increase. The temperature rise that occurs in the metal drilling process is related to the rate, drill speed, and drill diameter, the drill speed which has a significant influence. One of the efforts to reduce the temperature of the drilling process is by using the Minimum Quantitative Lubricant (MQL) method. The MQL method is more effective by utilizing the surrounding air by making a fan that produces cold air. The method of this research is Computational Fluids Dynamic (CFD) simulation using flow simulation, with parameters 3 shapes of the blades, and variations in the number of blades 3,5 and 7. The purpose of this study is to analyze the shape and number of blades on a portable chip fan for metal drilling cooling processes. The CFD simulation results obtained from Model 2 and the number of blades 3 with a minimum temperature of 29.87°C and a maximum temperature of 30.19°C.